Postoperative Imaging Findings Associated with Transpalpebral Craniotomy Approach to Anterior Cranial Fossa - Monks, Dennis; Weyer, Allison; Thurlow, Peter; Aziz, Khaled; Happ, Erik; Goldberg, Michael (Journal of Neurological Surgery Part B: Skull Base, 2017)
Background and Purpose The transpalpebral “eyelid” approach is a novel alternative to the traditional ciliary or supraciliary incision for supraorbital frontal craniotomy and access to the anterior cranial fossa. Though a prior publication from our institution has described the surgical approach in detail along with cosmetic and clinical outcomes, postoperative imaging findings have not yet been described. As this surgical technique becomes more widely practiced, it is essential for neuroradiologists, oculoplastic surgeons, and skull base neurosurgeons to be familiar with the expected postoperative imaging findings, especially those that prompt subsequent intervention.Materials and Methods A retrospective, institutional review board approved review was performed of 102 patients who underwent transpalpebral surgical approach at Allegheny General Hospital from June 2007 through May 2015. Operative reports, pathology reports, preoperative imaging, postoperative imaging, and postoperative clinical documentation were reviewed.Results Forty-nine percent of patients had solely benign expected postoperative imaging findings, 37% had various atypical findings not requiring further intervention (most commonly asymmetric globe protrusion and bone cement in a paranasal sinus), 6% had findings prompting minimally invasive bedside procedures (most commonly pseudomeningocele), and 8% had findings requiring surgical intervention.Conclusion The majority of imaging following the transpalpebral approach showed typical, benign findings, such as minimal pneumocephalus and asymmetric globe protrusion. Nonetheless, members of the clinical team should be aware of the small number of findings requiring intervention, especially pseudomeningocele.
Keywords: radiology; anterior cranial fossa; minimally invasive; minicraniotomy